Islamic Banks In Muslim Countries And Indonesia - Desmadi Saharuddin; meirison meirison (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
This article aims to provide an overview of Islamic banking, which has shed light on Muslims in avoiding usury with inflation and oppression. The negative impact of cartels can be reduced. Suppose traditional banks have only one way to work, interest-bearing loans, although in many forms. The problem inherent in Islamic banking activities is whether they can be separated from the influence of conventional banks in various activities carried out, given the interrelationships between Islamic banks and traditional banks. By conducting a literature study, we analyzed banking data contained in documents, books, and journals using a qualitative approach using descriptive analysis methods. We try to provide an interpretation of the work of Islamic banks operating in various Islamic worlds and Indonesia. We found Islamic banks to be less compliant with the fatwas and instructions given by the existing Islamic boards. We find that Islamic banks have difficulty complying with shari'ah rules because they are constrained by the conventional banking financial system full of usurious Mu'amalah. Constrained by capital from the central bank, high operating costs, investment problems in the real sector, risk of loss and others. The focus of this research is the causes of the condition of Islamic banks in the Islamic world, which are trapped in a Ribawi labyrinth